Evaluating dasatinib nanocarrier: Physicochemical properties and cytotoxicity activity on cancer cells - Altoham, Jamila; Abdalla , Ashraf; Abourehab , Mohammed; Tulbah, Alaa S. (International Journal of Health Sciences, 2024)
Objective: Dasatinib-(DAS) is a tyrosine kinase inhibitor usually used to treat leukemia. But, DAS is a poorly water-soluble drug. Therefore, oil-in-water emulsions were used for DAS to enhance its solubility and cancer treatment efficacy. This study aims to develop an appropriate DAS nanoemulsion (NE) that can overcome the issue of DAS solubility and provide an effective anti-cancer effect. Methods: Spherical particles dispersed in an aqueous media approach within an oily phase (oleic acid, Kolliphor RH40, and dipropylene glycol) were used to formulate DAS-NE, using high-energy methods. Different formulas were developed and an appropriate formula was analyzed to identify its physicochemical properties. Raw DAS and nano-formula cytotoxicity were evaluated via MTT assay against three cancer cell lines, MCF7 (human breast adenocarcinoma), HT29, and SW480 (human colorectal carcinomas), in addition to MRC5 (Normal human fetal lung fibroblast). Results: Different DAS-NEs (1-7) have been developed successfully. Formulas had a droplet size of a diameter ranging from 84.167±10.178nm to 273.433±45.267nm. The drug content of the appropriate formula (DAS-NE3) was found to be 83.2%.The drug release result of DAS-NE3 when compared to raw DAS was about 58%, falling to 13% after 24-hours.The DAS-NE3 showed cytotoxicity against the three cancer cells below 26.11μM but showed 30-fold significantly increased selectivity against MRC5 normal cells compared to that of raw DAS. Conclusion: This study shows that the DAS-NE3 formula may provide a potentially effective and sustained drug delivery for cancer treatment. This provides valuable information to the scientific community and pharmaceutical industry.